One-pot synthesis of reduced graphene oxide nanosheets anchored ZnO nanoparticles via microwave approach for electrochemical performance as supercapacitor electrode - Kumar, Rajesh; Youssry, Sally M.; Abdel-Galeil, Mohamed M.; Matsuda, Atsunori (Journal of materials science. Materials in electronics, 2020)
In this article, we have demonstrated single-step as well as scalable synthesis of zinc oxide nanoparticles (ZnO NPs) supported on highly thin/transparent reduced graphene oxide (rGO) nanocomposite (ZnO@rGO) via direct microwave irradiation using decomposition of zinc acetate dihydrate (Zn(CH 3 CO 2 ) 2 ·2H 2 O) along with reduction of graphite oxide. The surface microstructure of prepared ZnO@rGO nanocomposite was analyzed by X-ray diffraction, transmission electron microscopy, scanning electron microscopy, Raman spectroscopy, and X-ray photo electron spectroscopy. Different characterization analysis indicates that the ZnO NPs in the nanocomposite were dispersed on the surfaces of rGO nanosheets (NSs). Raman spectra reveal the structural defects level of rGO NSs was 0.78, while it was increased to 1.66 for ZnO@rGO nanocomposites. The synthesized ZnO@rGO nanocomposite exhibits specific capacitance of 102.4 F/g at the scan rate of 30 mV/s and shows good cyclic stability of 82.5% for 3000 cycles at high scan rate 100 mV/s.